THE MANAGEMENT OF SUSPECTED ENCEPHALITIS AT A REGIONAL DISTRICT GENERAL HOSPITAL. Issue 11 (14th October 2015) - Llewelyn, Dafydd; Fish, Mark
Abstract : Aim: To determine how suspected encephalitis is managed in a regional DGH against standard of ABN/BIA (Association of British Neurologists/British Infection Association) Guidelines (2012). Methodology: A retrospective audit of notes for 21 cases with suspected encephalitis (June to December 2013). Sampling utilised case coding, records of referrals to neurology and CSF analyses. Latency from time of admission to suspicion of encephalitis, CT, LP, MRI, aciclovir administration and neurological input were determined. Results: 12/21 patients received aciclovir within 6 hours (average 11.5h), 18/21 patients had a CT head scan before LP and in 14/21 cases aciclovir was started before LP. 18/21 cases underwent LP (6 on MAU, 11 by medical teams and 1 by neurology), 17/18 had CSF constituents requested, 9/18 had a paired serum glucose. 5 cases had repeat HSV PCR, 5 had HIV testing and 12/21 had an EEG. The average latency to MRI was 2.34 days and time to be seen by a neurologist was 2 days. Treatment was discontinued in 7 cases after negative HSV PCR and 5 after alternative diagnosis were made. Conclusions: Management of suspected encephalitis varied, we need to increase awareness ABN/BIA guidance and address the delay in neurology services seeing these patients.